Disappearing Earth - Phillips, Julia (New York Alfred A. Knopf, 2019)
"One August afternoon, on the shoreline of the Kamchatka peninsula at the northeastern edge of Russia, two girls--sisters, eight and eleven--go missing. In the ensuing weeks, then months, the police investigation turns up nothing. Echoes of the disappearance reverberate across a tightly woven community, with the fear and loss felt most deeply among its women. Taking us through a year in Kamchatka, Disappearing Earth enters with astonishing emotional acuity the worlds of a cast of richly drawn characters, all connected by the crime: a witness, a neighbor, a detective, a mother. We are transported to vistas of rugged beauty--densely wooded forests, open expanses of tundra, soaring volcanoes, and the glassy seas that border Japan and Alaska--and into a region as complex as it is alluring, where social and ethnic tensions have long simmered, and where outsiders are often the first to be accused."--
Keywords: Missing children -- Fiction; Missing persons -- Fiction -- Investigation; Kamchatka Peninsula (Russia) -- Fiction; Psychological fiction; Thrillers (Fiction)